Structural shocks and trend inflation - Bowen Fu; Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2023)
We propose an unobserved components model with stochastic volatility and structural shocks to explore the relevant factors that influence trend inflation in the USA. Using structural shocks that incorporate a broad set of information for the US economy, we find that four structural shocks have significant effects on trend inflation: productivity, price mark-up, government policy, and finance. During and in the aftermath of the Great Recession, trend inflation became more volatile after incorporating the structural shocks, implying that long-run inflation expectations tended to be less well-anchored in these periods.
Keywords: C11; C32; E31; E37; 330; trend inflation; structural shocks; dynamics of inflation expectations; unobserved components; stochastic volatility